Analisis Pengaruh Kecerdasan Emosional dan Keseimbangan Kehidupan Kerja - Nyimas Ratna Kinnary; Justine Tanuwijaya (Jurnal Bisnis dan Manajemen, 2022)
The study aimed to analyze the relationship between emotional intelligence on employee engagement, job satisfaction, and work-life balance. In addition, analyze the relationship of work-life balance on employee engagement, job satisfaction, and job performance, as well as the effect of performance on career development for employees of one of the world-class tire supplier companies in Suryacipta Industrial Estate, Karawang. The data processing method used structural equation modeling (SEM). The results showed that there is a significant effect of emotional intelligence on employee engagement and work-life balance, but does not have a significant effect on job satisfaction. Work-life balance also has a significant effect on employee engagement, job satisfaction, and job performance. In addition, job performance has a significant effect on career development. The work-life balance of employees needs to be considered by the organization so that employees can carry out two very different roles effectively to increase job performance. Future research is expected to be able to use a more specific questionnaire statement on emotional intelligence variables so that it can provide more representative results.